Effects of ammonia on the explosion and flame propagation characteristics of methane-air mixtures. (May 2017) - Luo, Zhenmin; Wang, Tao; Ren, Junying; Deng, Jun; Shu, Chimin; Huang, Anqi; Cheng, Fangming; Wen, Zhenyi
Abstract: To further study the effect of ammonium dihydrogen phosphate powder (NH4 H2 P2 O4 ) on methane explosion, a quartz tube test system with a length of 1400 mm and a 20 L spherical experimental system were employed to test the flame propagation and explosion characteristics of methane-ammonia-air mixtures. The mechanisms of the reaction processes were calculated using the Gaussian 03 quantum chemistry software. The results showed that NH3 played a key role in the process of methane explosion. The addition of ammonia reduced both the upper and lower gas explosion limits, diminishing the range of explosion limits and mitigating the risk of explosion. Ammonia weakened methane explosion, and the more ammonia that was added, the more effective the weakening effect. This weakening of explosions was more efficacious for higher concentrations of methane than it was for lower concentrations of methane. According to the Gaussian calculation results, ammonia and amino groups more readily consumed oxygen and hydro and hydroxyl free radicals compared with methane and methyl groups. These consumptions caused a positive microcirculation feedback loop, which greatly reduced the quantity of methyl radicals and formaldehyde, thereby interrupting the chain reaction during methane explosion. Highlights: The effects of ammonia on the explosion characteristics of methane were examined. An increased amount of ammonia decreased both the upper and lower explosion limits. The more ammonia that was added, the more effective the inhibition effect. Ammonia and amino groups more easily consume free radicals than methane and methyl groups.